FREIHEIT UND DIE ÜBERWINDUNG VON WIDERSPRÜCHEN - DER WEG ZUR ANDEREN MODERNE IN ANLEHNUNG AN WILHELM SCHMID (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Liberty and Overcoming Contradictions – The Way to Another Modern age According to Wilhelm SchmidThe visible change of Western society in the 21st century includes alongside economic and technological processes, political and socio-cultural processes. Despite the promotion of the modern concept of freedom, it is noted that the 21st century is marked by contradictions and a continuing tension between idealistic expectations and an imperative of progress. W. Schmid sees the cause of this situation in defining and interpreting the concept of freedom. He notes that the concept modern of life has consistently pursued the elimination of contradictions in life - which has often led to extreme positions. Through his maximum towards balance, Schmid tries to accomplish not only a cultural synthesis of values but also one between the rational pragmatism and idealist romance. This synthesis finds its expression in the vision of another modern age, not annulled but transformed, reflected and balanced.